PEDAGOGICAL CONDITIONS OF FORMATION OF FUTURE NURSES FOR PROFESSIONAL FULFILLMENT - Сірак, І. П. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
The purpose of research is the development; theoretical study and experimental verification of pedagogical conditions of formation of future nurses for professional fulfillment and methods of implementation of these conditions in the course of their professional education in medical colleges According to the subject; objectives; concepts and hypotheses; they are the following research objectives:to analyze the state of the problem of professional fulfillment in philosophical; psychological; pedagogical aspects in the scientific literature; to make a definitive analysis of the concept of "readiness of future nurses for professional self-realization"; to clarify the criteria and levels of this readiness; to define and justify pedagogical conditions and model formation of future nurses for professional fulfillment; to develop a methodology for implementing of pedagogical terms of preparing future nurses to the designated activity and test its effectiveness experimentally; to develop educational materials for students; teachers of medical colleges oncerning training future nurses for professional self- fulfillment. The hypothesis of the study is the assumption that the level of readiness of future nurses for professional self-fulfillment will increase because of their professional training focus in medical colleges to professional self- fulfillment and is provided by the formation of motivational attitudes of future nurses for professional self-realization with the help of simulation; cognitive activity of students by means of information and communication technologies; by development and implementation of extracurricular activities program in medical college to prepare future nurses for professional self-realization; by the creation of a reflexive-based environment in medical college; by application of methods of formation of readiness of future nurses for their professional self- fulfillment in the educational process